La médiation de Madame Bovary en Suède - Hans Färnlöf (Flaubert: Revue Critique et Génétique)
The present study provides a summary of earlier studies on Flaubert's transfer to Sweden and incorporates in addition data from the last decade. In doing so, the study focuses on two aspects: the introduction and current status of Madame Bovary and Flaubert in Sweden. The initial translation of the novel (1883) is compared with the most recent translation (2012) in the light of the respective literary fields. The reception of Madame Bovary is slow, as Flaubert is initially presented as “the author of Salammbô”. Following the introduction of Zola's naturalism in Sweden in the late 1870s, Flaubert is considered to be the central author of realistic literature in the mid-1880s. Madame Bovary is since then his main work up to the present days, which show a growing dominance of digital formats. Recently adapted on stage, the novel seems mediated today mostly through an ideological consumption filter, rather than being approached in its historical and literary context.